The influence of transformational leadership on Malaysian students’ entrepreneurial behaviour - Muhammad Ashraf, Fauzi; Tulasi, Martin (University of Cracow, Polan, 2021)
Objective: The objective of the article is to understand entrepreneurial abilities of students in Malaysian higher education system. Hence, the role of transformational leadership, psychological empowerment, and knowledge sharing in inducing this behaviour are imperative to ensure that students are inclined to and familiar with entrepreneurial activities during their studies.